Jack Ryan : Weapons Grade - Book 36 Book 36 - Clancy, Tom, 1947-2013; Bentley, Don (New York, New York : G. P. Putnams Sons, 2023)
The quiet of a Texas night is shattered by the sounds of screeching brakes, crumpling metal and, most shockingly, rapid gunfire. The auto accident Jack Ryan Jr., thought he witnessed turned out to be a professional hit. Jack may be too late to save the victim, but hell be damned if hes going to let the hitters escape justice. Hes got just one lead--a meeting the victim was going to. When Jack shows up instead, hes drawn into the seedy underbelly of a small Texas town and the cold case of a college student who vanished from its streets. Jack is left with nothing but questions. Who wants it to look like the victim was drunk? Why does someone want an innocent witness killed? And most of all, whats a team of South African hitmen doing in the Lone Star State? His quest for answers will take Jack from a quiet Texas road to the middle of an international conspiracy and may just cost him his life.
Keywords: Ryan, Jack, Jr. (Fictitious character) -- Fiction; Intelligence officers -- Fiction; Conspiracies -- Fiction; Cold cases (Criminal investigation) -- Fiction; Assassins -- Fiction; Spies -- Fiction; Political crimes and offenses -- Fiction; Texas -- Fiction; Thriller